Critical perspectives from Africa and Europe - Smith, Tom; Solomon, Hussein (Exporting global jihad, 2020)
This timely 2 volume edited collection looks at the extent and nature of global jihad, focusing on the often-exoticised hinterlands of jihad beyond the traditionally viewed Middle Eastern 'centre'. As ISIS loses its footing in Syria and Iraq and al-Qaeda regroups this comprehensive account will be a key work in the on-going battle to better understand the dynamics of the jihads global reality. Critically examining the global reach of the jihad in these peripheries has the potential to tell us much about patterns of both local mobilisation, and local rejection of a grander centrally themed and administered jihad. Has the periphery been receptive to an exported jihad from the centre or does the local rooted cosmopolitanism of the jihad in the periphery suggest a more complex glocal relationship? These questions and challenges are more pertinent than ever as the likes of ISIS and many commentators, attempt to globally rebrand the jihad and as the centre reasserts its claims to the exotic periphery.